Organic vegetables demand in urban area using a count outcome model: Case study of Burkina Faso - Janvier Kini; Nicky Pouw; Joyeeta Gupta (Agricultural and Food Economics, 2020)
This paper designs and tests a model for count outcomes to analyse the effective demand for organic vegetables in the city of Ouagadougou, Burkina Faso. From a 'short value chain' perspective, we show that the distance travelled by consumers to organic vegetable production sites primarily managed by women farmers' associations, is a key determinant of organic food demand. Furthermore, the effect of the distance travelled on the demand is stronger for women than for men. In addition, consumers' health awareness and the intended use of these vegetables are significant determinants of their demand. Moreover, social-relational factors affect the purchase decision both ways, including issues of trust and access to market information. Thus, this paper first introduces the socially subjective considerations of the demand for food in the close interaction between producers and consumers of organic food. Second, it contributes to filling the knowledge gap on the factors influencing consumer behaviour in purchasing organic food in urban production sites in developing countries.
Keywords: 330; Organic vegetable; Short value chain; Urban food demand; Distance; Health; Burkina Faso